The stability of the steady motion of a liquid plug in a capillary tube - Campana, Diego Martin (2007)
In this work, we present a methodology to analyze the stability of the steady-state propagation of a liquid plug in a capillary tube lined with a uniform film of the same liquid. To this end, the steady-state solutions are computed and the corresponding film thickness is obtained for different plug lengths and fixed capillary and Reynolds values. The evolution of this variable as a function of the plug length for each capillary and Reynolds number is the key to plug stability determination.